Criminal Liability for Driver Negligence Resulting in Death in Road Traffic Accidents - Andika Eka Putra Amisi; Nur Handayat; bachrul Amiq (Rechtsvinding, 2026)
Traffic accidents that result in the death of victims are still a serious problem in the Indonesian criminal law system. One of the dominant factors causing traffic accidents is the negligence of motor vehicle drivers in complying with traffic rules and the principle of caution on the highway. This study aims to analyze the legal arrangements and forms of criminal liability of motor vehicle drivers who, due to their negligence, cause traffic accidents and cause death. The research method used is normative legal research with a statutory approach and a conceptual approach. The legal materials analyzed include the Criminal Code, Law Number 22 of 2009 concerning Road Traffic and Transportation, as well as relevant court decisions. The results of the study show that the legal regulation regarding the criminal liability of negligent drivers has been specifically regulated in Article 310 paragraph (4) of the Road Traffic and Transportation Law as a lex specialis of the general provisions in the Criminal Code. The application of criminal liability is based on the fulfillment of the elements of negligence, the ability to be responsible, and the absence of a forgiving reason. This study emphasizes the importance of consistent and proportionate law enforcement to provide legal certainty, a sense of justice for victims, and a deterrent effect for traffic accident perpetrators.